STUDY OF BOIL- OVER PHENOMENON, THE ALGERIAN. PETROLEUM AS A MODEL FOR INSPECTION - Ghodbane, M (جامعة الوادي - university of el oued, 2015)
With the development of oil facilities, development of industrial security and evolved methods of preventionn but industrial risks always remain present. In this work, we we'll examine a very serious phenomenon, which “Boil-Over”. This phenomenon appears in petroleum reservoirs (oil has a high viscosity), and that in the event of a fire on the roof of the tank with the presence of water at the bottom of the tank. We chose the Algerian Petroleum to conduct this study. We will talk to the disastrous results of this phenomenon, and risks to all people, equipment and the environment.
Article
Keywords: Safety, Environment; Storage, Fire, Boil-Over.